Polygenic risk for schizophrenia and subjective well-being in a general population sample - Serimaa, Oona; Keltikangas-Järvinen, Liisa; Lyytikäinen, Leo-Pekka; Hietala, Jarmo; Sormunen, Elina; Kähönen, Mika; Raitakari, Olli; Lehtimäki, Terho; Saarinen, Aino (CAMBRIDGE UNIV PRESS, 2026)
Background Previous evidence has reported associations of a polygenic risk score for schizophrenia (PRSSCZ) with negative developmental outcomes, such as psychiatric symptoms, adverse health behaviors, and reduced everyday functioning. We now investigated the relationship of PRSSCZ with subjectively experienced well-being.
Methods Participants (n = 1866) came from the prospective population-based Young Finns Study (YFS). Subjective well-being in adulthood was assessed in terms of life satisfaction, optimism, and self-acceptance (when participants were 20-50 years old). A PRSSCZ was calculated based on the most recent genome-wide association study on schizophrenia. Covariates included age, sex, early family environment, adulthood socioeconomic factors, and adulthood health behaviors.
Results The PRSSCZ did not predict any domain of subjective well-being, including life satisfaction, optimism, and self-acceptance. After adding covariates in a stepwise manner or including/excluding participants with diagnosed non-affective psychotic disorders, all the associations remained non-significant. Age- and sex-interaction analyses showed that PRSSCZ was not associated with subjective well-being in either sex or in any age between 20 and 50 years.
Conclusions While high PRSSCZ has been linked to multiple adversities in previous studies, we did not find any association between high PRSSCZ and subjective measures of life satisfaction, optimism, and self-acceptance.